THE EFFECT OF CR AND DAR ON ROA ON COAL MINING SUB SECTOR COMPANIES LISTED ON BEI - Hasmirati Hasmirati (Institut Teknologi Adhi Tama Surabaya, 2021)
This study aims to determine and analyze how much influence the Return Current Ratio (X1) and Debt to Total Assets Ratio (X2) both simultaneously and partially have on Return On Assets. This research is a quantitative study, using ratio analysis. The analysis method uses multiple linear regression. The results showed that the Current Ratio (X1) and Debt to Total Assets Ratio (X2) simultaneously did not have a significant effect on the Return on Assets of the Coal Mining sub-sector companies listed on the Indonesia Stock Exchange of 0.057. Current Ratio (X1) partially has a significant effect on Return On Assets of 2.369. Debt to Total Assets Ratio (X2) partially has a significant effect on Return On Assets of 2.347. Keywords: CR, DAR, dan ROA